The Awareness of Faculty Members and Those in Authority at King Saud University Regarding the Importance of Reputation Management and Its Impact on Educational Institutions - Alotibi, Maha Naif; Albeshir, Saud Ghassan (Journal of Educational and Psychological Sciences, 2024)
The study aimed to explore the awareness of faculty members at King Saud University regarding the importance of reputation management, as well as its impact on the educational institution from their perspective. The study employed a descriptive methodology with a sample size of 102 faculty members at King Saud University. The researcher utilized a questionnaire as the data collection tool. The study reached several findings, including: The awareness level of faculty members at King Saud University regarding the importance of reputation management for educational institutions was very high. Most members affirmed that reputation is not a temporary phenomenon but requires time to build, highlighting the significance of consistency and stability in reputation-building for the educational institution. Moreover, the degree of impact of reputation management on the educational institution, from the perspective of faculty members at King Saud University, was very high. Reputation management was recognized as playing a pivotal role in establishing the institution's prestigious social standing, illustrating its substantial importance in garnering respect and acknowledgment from the community.The study recommended the necessity of enhancing awareness regarding the importance of building the reputation of the educational institution as a fundamental element in fostering trust, attracting qualified personnel, and achieving effective communication.
Keywords: Reputation Management; Educational Institutions; Faculty Members